Responding to Global Public Bads : Learning from Evaluation of the World Bank Experience with Avian Influenza 2006-13 - Independent Evaluation Group (World Bank, Washington, DC, 2016)
The World Bank’s efforts to combat avian influenza and help countries to build capacity to prevent and mitigate pandemics offers a useful example in understanding how the agency can contribute to the provision of global public goods. This review aims to inform the provision of these goods by offering lessons from evaluation of the avian influenza experience. The experience also offers an example of the Bank playing a key role in the international response to an unfolding international crisis in a technical area with which it was largely unfamiliar. And provides a case study on how the Bank struggles to work effectively across sectors, both within the institution itself and in the client countries it operates in. The report aims to inform the design of any future avian influenza and zoonotic disease and pandemic preparedness interventions, and also to discuss the wider strategic lessons from the intervention that are relevant to programs responding to emergencies, providing global public goods, or cooperating with external technical agencies. The report also aims to assess the current state of the pandemic preparedness agenda, and to provide guidance on possible ways forward. The report also draws on additional interviews with Bank staff and international agency staff, on World Bank project and program documentation and reports, on the wider literature on avian influenza, and on other documents.